Member reflections with elite coaches and gymnasts: looking back to look forward. Issue 1 (1st January 2020) - Cavallerio, Francesca; Wadey, Ross; Wagstaff, Christopher R. D.
ABSTRACT: This paper is a confessional tale that focuses on challenges encountered during the process of conducting member reflections, and on the lessons learned from these. Recent discussions on enhancing the rigor of qualitative research conducted from an interpretivist stance encourage the use of member reflections, rather than the previously widely adopted member checking. Yet, practical examples of how to use this technique are scarce in the sport, exercise and health literature. As a consequence, researchers trying to achieve rigor in their work might struggle, especially if inexperienced. In this work, the first author provides a personal narrative that explores the questions and doubts encountered when engaging with member reflections during her PhD degree. Drawing on the first author's reflective journal, a challenging situation is portrayed, and recommendations for other neophyte researchers are forwarded through four main lessons learned: (a) lessons on rigor in qualitative research, (b) lessons on tellability and layers of understanding, (c) lessons on the importance of confrontations and knowledge exchange, and (d) lessons on relational ethics.